Anti-Viral Activities of Umbilical Cord Mesenchymal Stem Cell-Derived Small Extracellular Vesicles Against Human Respiratory Viruses - Oh, Soo-Jin; Lee, Eun-Na; Park, Joo-Hoo; Lee, Jae Kyung; Cho, Geum Joon; Park, Il-Ho; Shin, Ok Sarah (Frontiers in Cellular and Infection Microbiology, 2022)
The endemic and pandemic caused by respiratory virus infection are a major cause of mortality and morbidity globally. Thus, broadly effective antiviral drugs are needed to treat respiratory viral diseases. Small extracellular vesicles derived from human umbilical cord mesenchymal stem cells (U-exo) have recently gained attention as a cell-free therapeutic strategy due to their potential for safety and efficacy. Anti-viral activities of U-exo to countermeasure respiratory virus-associated diseases are currently unknown. Here, we tested the antiviral activities of U-exo following human influenza A/B virus (IFV) and human seasonal coronavirus (HCoV) infections in vitro. Cells were subject to IFV or HCoV infection followed by U-exo treatment. U-exo treatment significantly reduced IFV or HCoV replication and combined treatment with recombinant human interferon-alpha protein (IFN-) exerted synergistically enhanced antiviral effects against IFV or HCoV. Interestingly, microRNA (miR)-125b, which is one of the most abundantly expressed small RNAs in U-exo, was found to suppress IFV replication possibly via the induction of IFN-stimulated gene (ISG). Furthermore, U-exo markedly enhanced RNA virus-triggered IFN signaling and ISG production. Similarly, differentiated air-liquid interface (ALI) cultures of human nasal epithelial cell studies confirmed broadly effective anti-viral and anti-inflammatory activities of U-exo against IFV and HCoV, suggesting the potential role of U-exo as a promising intervention for respiratory virus-associated diseases.